2021
DOI: 10.5811/westjem.2021.3.50981
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional Analysis of Food Insecurity and Frequent Emergency Department Use

Abstract: Introduction: Emergency department (ED) patients have higher than average levels of food insecurity. We examined the association between multiple measures of food insecurity and frequent ED use in a random sample of ED patients. Methods: We completed survey questionnaires with randomly sampled adult patients from an urban public hospital ED (n = 2,312). We assessed food insecurity using four questions from the United States Department of Agriculture Household Food Security Survey. The primary independent var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…This is in contrast to earlier studies by Estrella et al that showed higher ED usage among FI individuals (adjusted OR 1.48 [95% CI 1.20-1.83]) and by Ghani et al who found higher ED utilisation rates among those with chronic conditions who experienced FI as compared to those who were food secure (adjusted incident rate ratio 1.90 [95% CI 1.20-3.01]). 19,21 Our study did not show differences in FI based on acuity level or medical comorbidities, which was similar to other ED-based studies of FI. 8,10 This differs from population studies of children and adolescents in NZ that showed an association with FI and comorbidities 5,6 ; perhaps this difference could be explained by the ED-based setting and inclusion of participants of all ages.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in contrast to earlier studies by Estrella et al that showed higher ED usage among FI individuals (adjusted OR 1.48 [95% CI 1.20-1.83]) and by Ghani et al who found higher ED utilisation rates among those with chronic conditions who experienced FI as compared to those who were food secure (adjusted incident rate ratio 1.90 [95% CI 1.20-3.01]). 19,21 Our study did not show differences in FI based on acuity level or medical comorbidities, which was similar to other ED-based studies of FI. 8,10 This differs from population studies of children and adolescents in NZ that showed an association with FI and comorbidities 5,6 ; perhaps this difference could be explained by the ED-based setting and inclusion of participants of all ages.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with results from studies performed in the USA showing a higher prevalence of FI in the ED setting compared to the community setting, with rates as high as 45.6% in paediatric EDs and 50.8% in adult EDs. 9,19 EDs often serve as society's safety net and as such may see a disproportionate number of food insecure individuals. Thus, EDs could be an ideal setting for a FI screening programme.…”
Section: Discussionmentioning
confidence: 99%
“…66,67 Food insecurity is also associated with greater emergency department visits and inpatient hospitalizations. [68][69][70][71][72][73][74] These "big ticket" forms of healthcare utilization in turn drive greater healthcare spending for individuals experiencing food insecurity. [75][76][77] All of these compensatory effects can create negative long-term health consequences.…”
Section: Question Responsesmentioning
confidence: 99%
“…8 The prevalence of FI and hunger in the ED population has historically been higher than among the general public. 2,10 Therefore, the ED environment represents a unique opportunity for physicians to identify patients with FI. Our goal in this study was to assess the impact of the COVID-19 pandemic on the prevalence of FI in the ED patient population.…”
Section: Introductionmentioning
confidence: 99%